Spatial Analysis of Landslide Vulnerability Using Weighted Overlay Based on GIS in Balik Bukit - Stefano Wahyudi; Azizah Dea Putri; Liana Sinaga; Aprido Lumbanraja (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2026)
Balik Bukit District in West Lampung Regency is an area with high susceptibility to landslides, which are difficult to predict and pose significant threats to human safety. This study aims to comprehensively map landslide vulnerability zones as a foundation for mitigation strategies. The method used is the Weighted Overlay approach based on Geographic Information Systems (GIS), analyzing eight triggering parameters: slope steepness, slope aspect, slope length, lithology, distance from faults, soil type, soil depth, and rainfall. The research produced a risk map classifying the study area into three categories: low risk (4,878.442 ha), moderate risk (8,487.104 ha), and high risk (1,230.959 ha). Slope steepness was identified as the most dominant factor. This map is expected to serve as a strategic guide for the government and local communities in developing adaptive spatial planning and more effective disaster mitigation plans.